Simulation and comprehensive 4E study of a double flash geothermal-based organic Rankine cycle multi-generation system - Luis Buenaño; Diana Katherine Campoverde Santos; María Albuja; Mohammed Hasan Aldulaimi; Omar Salim Abdullah; Diego Mayorga; Omar H. AL-Zoubi; Shriya Mahajan; Ali Foladi (Energy Exploration & Exploitation)
The application of multi-generation systems has seen significant growth in recent years. This research explores an innovative Rankine organic cycle that generates electricity, hydrogen, and potable water by integrating geothermal and heat recovery as energy sources. The cycle's efficiency is assessed in two configurations: utilizing geothermal energy and not utilizing it. Calculations show that the highest exergy destruction, at 32.5%, is linked to the proton electrolyzer membrane (PEM). Additionally, the lowest exergoeconomic factor, at 7.9, is found for the PEM. The cycle generates 1.81 L/s of hydrogen and 4.52 kg/s of desalinated water. Increasing the temperature of the geothermal source from 125 °C to 161 °C leads to a 30.2% increase in hydrogen production and an 18.1% increase in desalinated water production. If geothermal energy is not used and all energy comes from heat recovery, carbon dioxide emissions will increase to 71%.